2022
DOI: 10.5269/bspm.45062
|View full text |Cite
|
Sign up to set email alerts
|

Zeroth-order general Randi´c index of trees

Abstract: Randi\'{c} indices belong to the most well-known topological indices. We study a very general index called the zeroth-order general Randi\'{c} index. We present upper and lower bounds on the zeroth-order general Randi\'{c} index for trees with given order and independence number, and for trees with given order and domination number. We also show that the bounds are best possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Moreover, the corresponding extremal graphs are characterized. In the paper, [13], upper and lower bounds on the zeroth-order general Randić index for trees with a given order and domination number are presented. In addition, the authors showed that the bounds are the best possible.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the corresponding extremal graphs are characterized. In the paper, [13], upper and lower bounds on the zeroth-order general Randić index for trees with a given order and domination number are presented. In addition, the authors showed that the bounds are the best possible.…”
Section: Introductionmentioning
confidence: 99%